2012
DOI: 10.1016/s0019-4832(12)60060-1
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmally dilated major aorto-pulmonary collateral in tetralogy of Fallot

Abstract: Haemodynamically significant systemic-to-pulmonary artery collaterals may present as a cause of cardiorespiratory compromise in tetralogy of Fallot (TOF) with pulmonary atresia. We present here a case of TOF with pulmonary atresia with aneurysmally dilated aorto-pulmonary collateral causing compression over trachea, presenting as dry irritating cough who died suddenly with haemoptysis probably due to rupture of hypertrophied bronchial collaterals or direct erosion of large major aorto-pulmonary collateral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 7 publications
(5 reference statements)
0
19
0
Order By: Relevance
“…Occasionally they may arise from the abdominal aorta or uncommonly from other systemic arteries such as carotid or coronary arteries (5). Aneurysmal dilatation of MAPCA has been described which may occasionally cause symptoms due to the compression of adjacent structures (1). It may also cause life threatening hemoptysis due to rupture or even death (1,2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally they may arise from the abdominal aorta or uncommonly from other systemic arteries such as carotid or coronary arteries (5). Aneurysmal dilatation of MAPCA has been described which may occasionally cause symptoms due to the compression of adjacent structures (1). It may also cause life threatening hemoptysis due to rupture or even death (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal dilatation of MAPCA has been described which may occasionally cause symptoms due to the compression of adjacent structures (1). It may also cause life threatening hemoptysis due to rupture or even death (1,2). These collaterals may also predispose to pleural effusions (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature found 2 cases of tracheobronchial compression from dilated pulmonary arteries in adults. Symptomatic tracheobronchial compression was reported in an 18-year-old female with newly diagnosed absent pulmonary valve syndrome, 14 and asymptomatic left bronchial compression was reported in a 55-year-old male with chronic thromboembolic disease and congenital pulmonary stenosis with consequent pulmonary arterial dilatation. 15 Left main coronary artery compression and left recurrent laryngeal nerve compression are otherwise well-reported complications of pulmonary arterial dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…9 In adults, patients are likely to be unsuitable for surgical intervention. In the 2 cases previously reported in the literature, one patient died soon after diagnosis, 14 and the other managed with pulmonary vasodilators. 15 Endobronchial stenting has not been performed.…”
Section: Discussionmentioning
confidence: 99%